An Analysis of the Lexical and Contextual Meaning of Expert Witness Examination Part in Travis Reinking Murder Criminal Trial - Novalinda Nadya Putri (Publikasi Indonesia, 2026)
This research aims to analyze the lexical and contextual meanings in the language used by an expert witness during the examination phase of the Travis Reinking murder trial. The trial attracted national attention in 2018 after Travis Reinking allegedly opened fire at a Waffle House in Tennessee, resulting in four fatalities and multiple injuries. This study focuses on how language is employed by the expert witness to convey forensic information within a legal setting. The research adopts a descriptive qualitative method, with data obtained from the Law & Crime Network YouTube video titled